Pengaruh perubahan modal kerja,ukuran perusahaan dan risiko bisnis terhadap kebijakan pendanaan pada perusahaan pertambangan yang terdaftar di bursa efek Indonesia periode 2009-2011 - Bobby Sumardi; Hardi '; Sem Paulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of changes in working capital, company size and business risk to the company”s funding policy on mining.The object under study is a group of mining companies listed on the Indonesian Stock Exchange (BEI) in the year 2009-2011 with some predetermined criteria,so we get the end of the study sample as many as 14 companies during the period 2009-2011. The analytical method used is regression analysis.Priod to the statistical t-test againts multiple rergression equation,the test is done first classical assumption of normality of the data,autocorrelation,multicollinearity and heteroscedasticity. Based on the analysis,it is known that the working capital turnover and firm size no significant effect on the funding policy.Meanwhile,the business risk significantlyinfluence funding policy.The coefficient of determination is 0,11 which shows the influence of the independent variables used in the model of funding research on policy as the dependent variable was 11% while the rest 89% is explained by other variables not included in this research model.Keywords : Changes in Working Capital,Company Size,Business Risk Financing Policy